Wirkmedienbasierte Umformung von Blechhalbzeugen unter Anwendung magnetorheologischer Flüssigkeiten als kombiniertes Wirk- und Dichtmedium - Rösel, Sebastian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)
The objective of these investigations is to enhance the process window of blank hydroforming processes to increase the robustness and the forming possibilities. This aim shall be reached by using a magnetorheological fluid as active fluid medium. If it is possible to shift the sealing limit to higher cavity pressures and lower flange contact pressures the necessary investment and the blankholder force can be decreased. Thereby an extensive use of this technology becomes possibl